Distal-continual colon interposition for esophageal reconstruction after esophagectomy: Two case reports - Guo, Bin; He, Ming; Zhao, Jidong; Ma, Minting; Gao, Zhanjie (Frontiers in Surgery, 2023)
Background Colon interposition is a complex and time-consuming procedure requiring at least three or four digestive anastomoses. However, the long-term functional outcomes are promising, with an acceptable operative risk. Case presentation Herein, two cases of esophageal carcinoma that received esophagus reconstruction using the distal continual colon interposition technique have been described. The transverse colon was lifted to the thoracic cavity for the end-to-side anastomosis with the esophagus, and a closure device was used to close the colon instead of severing and isolating the distal end. The duration of the operation was 140 and 150 min, respectively. The blood supply of the colon was maintained during the intervention. The tension-free anastomosis was performed without severe complications, and oral food intake was resumed on postoperative day 6. Neither anastomotic stenosis, antiacid or heartburn, dysphagia, or emptying obstacles nor complaints of diarrhea, bloating, or malodor were reported during the follow-up period. Conclusions The modified distal-continual colon interposition technique may have the advantages of a short operation time and potential prevention of serious complications caused by the torsion of mesocolon vessels.